(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify the concepts of space and time in children. To detect statistically significant differences in the development of the concepts of space and time according to the gender variable (male- female) and to identify the existence of an evolutionary path in the temporal and spatial concepts in children (5-6-7) and the research sample consisted of (60) children of Riyadh and primary schools The Directorate of Education of Baghdad first class for the academic year (2018-2019) and to achieve the objectives of the research the researchers tested the concepts of time and space and the study found that children (5) years old do not have the concepts of temporal and spatial and begin to have temporal and spatial concepts at the age of (6) years In the preliminary stage, the results did not show differences between the male and female averages in the development of space and time